"Land is life, conservancy is life." : the San and the N! Jaqna conservancy, Tsumkwe District West, Namibia - Welch, Cameron (Basel Namibia studies series, 2018)
Community-based natural resource management or CBNRM, with its attention to community participation, its call for de-centralization of rights to local resource users through democratic and equitable structures, and its potential to deliver benefits to local livelihoods and national conservation interests now forms the predominant strategy for rural development in the communal areas of Namibia. This framework is presumed by the Namibian government and international bodies concerned with conservation and development to deliver measurable and positive economic, environmental, and political results for the State and all of its citizens. For residents of many of the communal areas of Namibia the "Conservancy" has become the primary avenue through which rural residents engage with development and conservation in various efforts to improve local livelihoods and to conserve natural resources. CBNRM has taken on particular form and significance for the San in Namibia. This book examines the current position of the San as marginalized Indigenous peoples in Namibia. In doing so, it explores how CBNRM has become a nexus through which questions of Indigeneity, conservation and development have come to bear on San communities. Focusing on the experiences of a group of predominantly San communities in the North-East of Namibia, the historical and contemporary situations of the San of the Na Jaqna Conservancy and their engagement with CBNRM are examined. In looking to the future, this work seeks to understand what mechanisms and institutions give Indigenous groups, such as the San, a foothold in the State and an avenue though which to navigate and shape their own modernity(ies). This work explores the modalities through which conservation comes together with interests of Indigenous groups and how these groups deploy leverage gained through invoking conservation as discourse and practice. In examining San engagements with the Conservancy structures in N+a Jaqna, this study seeks answers not only to the question of what San engagements with CBNRM can tell us about the potential of the CBNRM framework itself for facilitating rural development and conservation, but also the question of what engagement with CBNRM can tell us about how the San of Namibia actively engage in rural development. The following work focuses not solely on how policies and governmental or non-governmental interventions have impacted San realities and life ways, but also the ways in which the San of Na Jaqna have negotiated, impacted, and shaped these processes